Estudio de factibilidad para la creación de una empresa de comercialización y trasformación (Modulares) de madera plástica en la ciudad de Armenia "Moduplastic S.A.S" (2013)
With the creation of value and dynamism in the furniture industry for homethis stands out as one of the most important and dynamic sectors in the Department of Quindío. However, the use of substitute products with additional benefits, not reflected in the products marketed by the industry. The following chapters describe the processes required to develop a study of feasibility, the which seeks to innovate with plastic timber industry due to its physical benefits, such as: immunity to pests and vermin, fire retardant, a lifespan far longer, resistant to water, chemicals and plant protection agents, heat-resisting and similar to natural wood utilization, since you can brush, polishing, sanding, cutting, drilling, painting, such as natural wood. For this reason it is a perfect substitute, due to the previously mentioned aspects, without forgetting that being a product made with recovered elements, is would be helping to reduce the environmental impact compared to discarded waste, such as plastic. What he wants this feasibility study is to design modular products made from this material, such as: closets, commodes, TV tables and computer tables, this study contains seven (7) chapters which mention general aspects such as the product and its uses,demand, supply, manufacturing processes, business structure, financial structure, among others.